Embolization for the treatment of delayed hematuria renal artery pseudoaneurysm following blunt trauma - Hardiyanti, Ginanda Nabilla; Ahmad Kabir, Ahmad Khairulnaim; Mohamed Mustafa, Nur Liyana; Tharek, Anas; Al-Khafiz Kamis, Mohd Fandi; Nasir Aslam, Achmad Bayhaqi; Muda, Ahmad Sobri (The Interventionalist, 2023)
Background: The occurrence of a renal artery pseudoaneurysm after blunt renal trauma is an infrequent complication. The occurrence of delayed bleeding is typically observed within a period of 2 to 3 weeks following an injury and is commonly attributed to the presence of an arteriovenous malformation (AVM) or pseudoaneurysm. They are frequently observed in cases of injuries of greater severity or trauma that penetrates the body. The application of angiographic catheterization is efficacious in the detection of pseudoaneurysms in the renal artery. The management of renal pseudoaneurysms necessitates the consideration of distinct clinical associations, including the location and size of the lesion as well as the presence of symptoms.